DYNAMIC POWER MANAGEMENT AND CONTROL OF PV-WIND-BES BASED MICROGRID SYSTEM - Jawid Ahmadi, Mohammad (School of Engineering and Digital Sciences, 2023)
This study discusses the design and modeling of a microgrid system that is comprised of wind turbines, solar panels, and battery energy storage units (BESU). The purpose of the proposed system is to offer a consistent and dependable supply of power by integrating renewable energy sources with BES units in order to overcome the intermittent nature of these sources of energy. Continuity of power supply to vital loads is ensured by the microgrid's ability to function in either grid-connected or island mode, depending on the situation. The findings of the simulation indicate that the suggested system has the potential to achieve high levels of efficiency and reliability while simultaneously lowering carbon emissions and cutting down on energy expenses. In addition, the control strategy for the system is developed utilizing a hierarchical structure, which ensures the most efficient functioning of the photovoltaic, wind, and battery energy storage units. In order to increase the power quality, stability, and efficiency of this microgrid system, it is managed and regulated using an improved power management (IPM) algorithm. The efficiency of the proposed system is examined under a wide variety of scenarios, including the unpredictability of the weather patterns and the erratic nature of the electrical grid. According to the findings of the research, the PV-wind-BES-based microgrid system has the potential to be a workable option for off-grid and isolated locations that demand a dependable and environmentally friendly source of power.
Keywords: type of access: open access; renewable energy; battery energy storage units